Risk of Surgical Site Infection Following Open and Laparoscopic Cholecystectomy - Fazli Subhan, Maira Riaz, Atif Iqbal, Ehsanullah Malik , Irfan Ali, Abdul Ghani Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research was to assess the risk for infection at the surgical site following open vs. laparoscopic cholecystectomy. Study Design: Randomized control trial Place and Duration: Data was collected from different hospitals including Department of Surgery, Khyber Teaching Hospital and Jinnah International Hospital, Abbottabad in the period from March, 2022 to August, 2022. Methods: Total 94 patients of both genders had age 18-70 years were included. We have taken informed written consent from the included patients for detailed demographics. We equally divided cases in two groups. Group I received open cholecystectomy in 47 patients and 47 patients of group II received laparoscopic cholecystectomy. Post-operative frequency of surgical site infection was compared among both groups. SPSS 23.0 was used to analyze all data. Results: In 94 included cases, 63 (67.02%) were females and 31 (32.98%) were males. Patients mean age in group I was 32.3±13.44 years while in group II mean age was 35.7±16.37 years. Diabetes, depression, hypertension and liver disease were the comorbidities among both groups. Post-operative duration of hospital stay was lower in group II 1.9±6.32 days as compared to group I 4.5±1.19 days. We found that frequency of surgical site infection in group I was higher in 12 (25.5%) cases as compared to group II in 3 (6.4%) cases. Conclusion: In this study, we found that laparoscopic cholecystectomy resulted in a lower rate of infection at the surgical site compared to open cholecystectomy. Keywords: Surgical Site Infection, Open cholecystectomy, Laparoscopic cholecystectomy